Fear and anthropology: a view from 1995 - Morphy, H; Banks, M; Barnes, RH (Anthropological Society of Oxford, 2022)
In broad terms the agenda of this paper is set by its title: by linking anthropology with fear, a concept with assumed general applicability, we are inevitably posing questions about the nature of cross-cultural categories. We have to confront the danger of imposing a Western concept on data from other societies. Any anthropological consideration of the human emotions must be concerned with the question of universality; with the relationship between the biological inheritance of humans and the autonomy of culture.